Influence of the Hinge Axis Transfer Modality on the Three-Dimensional Condylar Shift Between the Centric Relation and the Maximum Intercuspation Positions - Nikolina HOLEN GALEKOVIĆ; Vesna Fugošić; Vedrana Braut; Robert Ćelić (University of Zagreb. School of Dental Medicine, 2015)
Purpose. The purpose of the study was to determine whether the hinge axis registration and the transfer modality (facebow transfer vs. average mounting) from the subject to the articulator affect the three-dimensional condylar shift between the centric relation (CR) and the maximum intercuspation (MI) position. Material and Methods. The study was comprised of 32 fully dentate subjects (16 male and 16 female). Only the asymptomatic participants with normal occlusal relations (Angle class I) aged 20 - 33 (mean age 22.6 ± 4.7) met the inclusion criteria. Three-dimensional condylar shift (anteroposterior, superoinferior and mediolateral shift) between the centric relation position (CR) and the maximum intercuspation (MI) position was analyzed by means of Mandibular Position Indicator (SAM Prazisionstechnik GmbH, Muenchen, Germany). Results. The average three-dimensional condylar shift was 0.13 ± 0.12 mm for facebow transfer and 0.22 ± 0.23 mm for average mounting. There were no statistically significant differences noted between genders. The results of the Mann-Whitney test showed statistically significant differences for anteroposterior and superoinferior condylar shift (P < 0.001). However, the difference in the mediolateral shift was not statistically significant. Conclusions. In order to find discrepancies within the three-dimensional condylar shift, facebow transfer proved to be more accurate than the average mounting in the semi-adjustable articulator. However, the average value of three-dimensional shifts of the condyle did not differ from normal values and they did not have clinical significance. Thus, both ways of transfer modalities (facebow transfer and average mounting) in asymptomatic subjects with normal occlusion can be considered reliable.